KEMISKINAN DAN KETAHANAN PANGAN DI KALANGAN PETANI - Arsal, Thriwaty (Forum Ilmu Sosial, 2014)
The poverty problem is related to various variables. Generally, the cause of the poverty problem is divided into two, which are exogenous cause and endogenous cause. Based on the endogenous cause, poverty is divided into three. First, structural poverty, which is poverty that caused by the existence of policy, regulation, and the institutional that obstruct the productivity and mobility of the society. Second, cultural poverty, a poverty which is caused by behaviors and values which are applied by the society so they productivity is low. These are the reaction and adaptation upon their marginal position in social stratification. Third, natural poverty caused by the inadequate natural condition, such as the lack natural resources or the disadvantage of geographical condition. Meanwhile, for the endogenous cause, the poverty is caused by the weakness and physical flaws (physical defect or old age), the low the human resources quality (the low of education quality, health, skill, and competence), and the weak of individual character (fatalistic, apathetic, depending, helplessness, low self-esteem, easily discouraged, uncreative and not innovative, etc.). Although it can be differentiate, both the three of them are related and influential.